Percepção dos pais sobre a alteração da rotina de fisioterapia em crianças e adolescentes com paralisia cerebral durante a pandemia covid-19. - Borges, Valquiria Cuin (2022)
The change in the physiotherapy treatment routine caused by the coronavirus (COVID-19) pandemic has contributed to the regression of functional gains and the appearance of bone and joint deformities. The objective of this study was to identify the impact of the COVID-19 pandemic on the routine of physical therapy treatment and on the functional performance of children and adolescents with Cerebral Palsy (CP) from the perspective of the parents. This is a descriptive cross-sectional study that collected information about the routine of physical therapy consultations before and during the COVID-19 pandemic and the functional performance of children and adolescents with CP from 6 to 18 years old from the southeastern region of Brazil under the perceptive from parents. Conducted in a virtual environment through a form distributed through social networks and aimed at parents or legal guardians of children and adolescents with a clinical diagnosis of CP. The difficulty of distinguishing developmental milestones defined the exclusion of children under six years of age. A total of 161 forms were received. The analyzes were performed in the R program (version 4.2 for Mac iOS). The mean age of children and adolescents was 10.4± 3.3 years. The predominant gross motor function classifications were III (20.5%), IV (28%) and V (23.6%). A total corresponding to 87.5% had their physiotherapy treatment interrupted in the year 2020, their parents reported motor and functional changes (decreased strength, increased spasticity, worsening or appearance of deformities and decrease or loss of functional skills such as control of head, trunk, orthostatism and ambulation) and associated them with the interruption or modifications of the physical therapy routine for. The correspondence analysis of the variables showed the predominance of these damages to the GMFSC IV and V. The damages caused by the interruption of the physiotherapy treatment were greater among the most severe individuals (GMFCS 4 and 5), evidencing the need for validation of remote care and the elaboration of comprehensive public policies aimed at ensuring patient safety in essential services such as physical therapy during future emergencies.